Analysis of Factors Influencing Economic Growth in Middle Income Trap Asean - Ananda Nur Khofifah; M. Taufiq; Anisa Fitria Utami (International Journal of Economics, Business and Innovation Research, 2025)
The success of a country and the welfare of its population can be assessed through economic growth as the main indicator, for developing countries, equitable and stable economic growth is a priority for the transition to a developed country even though each country has different natural, economic, social, and cultural conditions, so that stability and sustainability of economic growth are needed to encourage sustainable development with one of its efforts through convergence economics. This study analyzes the convergence between ASEAN upper middle-income countries in 2013-2023 and variables that can accelerate the convergence of economic growth. The variables used include Foreign Direct Investment (FDI), trade openness, and corruption, which are suspected to affect economic growth. The approach used is a quantitative method with secondary data from the World Bank and Transparency International. The analysis methods used are sigma convergence, absolute beta convergence, and conditional beta convergence. The calculation of sigma convergence used the value of the coefficient of variation of GDP per capita, while the absolute beta and conditional beta convergence were analyzed using panel data regression with a selected fixed effect model. The results of the study show that there is a convergence of sigma, absolute beta and conditional beta convergence between ASEAN upper middle-income countries. It is known that the FDI variable has a positive and significant effect, while trade openness has a negative and insignificant effect, and corruption has a positive but insignificant effect on economic growth